Economic Security Study of the Territories of the Southern Federal District of the Russian Federation - Lyudmila V. OVESHNIKOVA; Elena V. SIBIRSKAYA; Alena A. SLEPOKUROVA; Svetlana V. KULIKOVA; Diana F. KHAKIMOVA (Communications of International Proceedings, 2020)
The article describes and analyses the economic security of the territories of the Southern Federal District of the Russian Federation and its place in the Russian economy. State activity in the study of the subject of economic security of the region has been noted. The indicators for the study of the economic security of the territories have been grouped into four main blocks: innovation, industry, social and economic. The result is a multi-dimensional grouping of the regions of the Southern Federal District according to the parameters of the socio-economic situation of the constituent entities of the Russian Federation, broken down by these groups of economic security indicators. Interregional inequalities in the research district have been identified and a number of problems and priorities for economic development have been identified.
Keywords: Economic security; gross regional product; cluster analysis; Southern Federal District (SFD); regions.